Dual inhibition of histone deacetylases and phosphoinositide 3‐kinases: effects on Burkitt lymphoma cell growth and migration. Issue 4 (11th November 2015) - Ferreira, Ana Carolina dos Santos; de‐Freitas‐Junior, Julio Cesar Madureira; Morgado‐Díaz, Jose Andres; Ridley, Anne J.; Klumb, Claudete Esteves
Abstract : The HDACi/PI3Ki combination suppresses BL cell proliferation and migration through alterations in PI3K signaling and HDAC function. Abstract : Burkitt lymphoma is a highly aggressive non‐Hodgkin lymphoma that is characterized by MYC deregulation. Recently, the PI3K pathway has emerged as a cooperative prosurvival mechanism in Burkitt lymphoma. Despite the highly successful results of treatment that use high‐dose chemotherapy regimens in pediatric Burkitt lymphoma patients, the survival rate of pediatric patients with progressive or recurrent disease is low. PI3Ks are also known to regulate cell migration, and abnormal cell migration may contribute to cancer progression and dissemination in Burkitt lymphoma. Little is known about Burkitt lymphoma cell migration, but the cooperation between MYC and PI3K in Burkitt lymphoma pathogenesis suggests that a drug combination could be used to target the different steps involved in Burkitt lymphoma cell dissemination and disease progression. The aim of this study was to investigate the effects of the histone deacetylase inhibitor suberoylanilide hydroxamic acid combined with the PI3K inhibitor LY294002 on Burkitt lymphoma cell growth and migration. The combination enhanced the cell growth inhibition and cell‐cycle arrest induced by the PI3K inhibitor or histone deacetylase inhibitor individually. Moreover, histone deacetylase inhibitor/PI3K inhibitor cotreatment suppressed Burkitt lymphoma cell migration and decreased cell polarization, Akt and ERK1/2 phosphorylation, and leads to RhoB induction. In summary, the histone deacetylase inhibitor/PI3Ki combination inhibits cell proliferation and migration via alterations in PI3K signaling and histone deacetylase activity, which is involved in the acetylation of α‐tubulin and the regulation of RhoB expression.